Experimental Study of Thermal Conductivity for Different Types of Cement Paste in Iraqi Markets - F. Hassan, Qais; F. Abbass, Ehssan; J. Taufeek, Kammal (Iraqi Journal of Civil Engineering, 2013)
In this study practical tests for thermal conductivity are done on twenty one specimens for seven types of cement mortar contains different types of cement available in local markets for Kirkuk city in the same standard conditions. Heat flow amounts within the specimens are calculated using Fourier law for conduction. Comparison between practical results and theoretical values depended in references for calculating thermal loads in concrete walls gave good agreement. Test results for specimen No. (7) for cement of Al-Sulaimanya company gave minimum value for thermal conductivity, which was (1.162 W/m.oC), and maximum value was for specimen No. (4) for Iranian cement, which was (1.55 W/m.oC) and for specimen No. (3) for cement of Bazian company, which was (1.52 W/m.oC). Results of thermal conductivity for all the other specimens were within the depended theoretical value. Minimum heat flow within the material was for specimen No. (7) for cement of Al-Sulaimanya company, while maximum value was for specimen No. (4) for Iranian cement. Key words: thermal conductivity test, cement, mortar, heat flow, Fourier law for conduction.